Formation of Leadership Skills of Students in the Process of Interdisciplinary Integration - ERMAK, Tetiana Mykolaivna (Journal of Research in Educational Sciences; Vol 16 No 1 (2025): JRES, Volume XVI, Issue 1(19), Summer 2025DO - 10.14505/jres.v16.1(19).01, 2025)
Interdisciplinary integration facilitates the development of systemic thinking, creativity, and leadership skills necessary for students to successfully adapt to contemporary challenges. The integration of arts, computer science, and English broadens students' opportunities for self-realization and enhances the effectiveness of the educational process. The relevance of this study is driven by the need for modern education to cultivate leadership skills among students that respond to the challenges of globalization, rapid technological advancements, and dynamic social realities. Leadership skills, such as critical thinking, initiative, communication, and teamwork, are key factors in personal development, socialization, and competitiveness in the modern world. The use of interdisciplinary integration in the educational process acts as an effective tool for creating conditions that foster the comprehensive development of these competencies, ensuring students' holistic worldview and their ability to address complex interdisciplinary tasks. The aim of the article is to explore the potential of integrating arts, computer science, and English in developing leadership skills among students in general secondary education institutions. The research utilized analysis of scientific publications and regulatory documents addressing interdisciplinary integration and leadership skill development, observation of educational processes, and synthesis of practical experience in project-based learning. The study substantiates the significance of interdisciplinary integration in forming leadership skills, such as initiative, creativity, critical thinking, communication, and teamwork. An example of the integrated project "Castles and Fortresses of Ukrainian Heritage" is detailed. This project aims to foster civic awareness, social and digital competencies. It combines research into cultural and historical heritage, the creation of informational booklets using digital tools, and presenting results in English.